A Study of Employee Character in Human Resource Development at the South Sumatra Provincial Archives Office - Rizki Amaliyah; Ryanti Isnania (Jurnal Pengabdian Masyarakat, 2026)
Purpose: The purpose of community service is to Analyze the character of employees at the South Sumatra Provincial Archives Office as a basis for human resource (HR) development. Method: The method used in this community service applies the HEXACO approach through observations and interviews with employees at the South Sumatra Provincial Archives Office. Practical Applications: The findings of this study can be applied to improve human resource development strategies by aligning training and development programs with the character traits of employees. Specifically, understanding employees’ conscientiousness and agreeableness allows the management of the South Sumatra Provincial Archives Office to design interventions that enhance discipline, teamwork, and cooperation. Conclusion: The effectiveness of human resource (HR) development programs is strongly influenced by employee character. This study applies the HEXACO personality theory (Honesty-Humility, Emotionality, Extraversion, Agreeableness, Conscientiousness, Openness to Experience). In the Archives Office environment, the most prominent traits are Conscientiousness (discipline and meticulousness) and Agreeableness (friendliness and cooperativeness), as reflected in employees’ diligence, adherence to rules, and ability to work effectively in teams.